New code structure for spectral amplitude coding in OCDMA system - Hasoon, Feras N.; Syed Alwee Aljunid, Syed Junid; Mohamad Khazani, Abdullah; Sahbudin, Shaari (The Institute of Electronics, Information and Communication Engineers, 2009)
Link to publisher's homepage at http://www.elex.ieice.org/